PERSEPSI PERAWAT, PASIEN DAN MASYARAKAT UMUM TENTANG PERILAKU CARING PERAWAT DALAM MEMBERIKAN ASUHAN KEPERAWATAN DI BANDUNG - Lumbantobing, Valentina; Adiningsih, Dian; Praptiwi, Atlastieka; Susilaningsih, Fransisca Sri (STIKes Maharani Malang, 2018)
Nurse is one of the professions responsible for improving peoples living standards, especially in the field of health. In carrying out the roles and responsibilities, the nurse is in the patients environment for 24 hours and is faced with various characters, complaints, different responses that require. Nurses are expected to be able to be caring to provide peace to the patient in his illness. The purpose of this study is to provide an overview of caring behavior of nurses perceived by nurses, patients and society when delivering nursing care at Bandung. The type of this research is quantitative descriptive research. By using accidental sampling, obtained, 95 nurses, 77 patients and 98 people general public around the faculty of Unpad nursing. Data were collected using Caring Behavior Inventory (CBI) instrument and analyzed using descriptive statistics and poured in tables, percentages and narratives. The results showed that nurse and patient perceptions related to caring nurse behavior in implementing nursing care were mostly good (56.8% and 50.8%), and public perception related to caring behavior of nurses was mostly (57.2%). It can be concluded that the perception of caring behavior of nurses in general has a different picture between nurses, patients and society in general. There needs to be an effort to improve and improve caring behavior of nurses who value directly by patients and the general public.